2013
DOI: 10.1074/jbc.m112.410720
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Development of Pulmonary Fibrosis via Cu,Zn-superoxide Dismutase-induced Alternative Activation of Macrophages

Abstract: Background:Macrophages play an important role in inflammation and injury as well as resolution of the response. Results: Mitochondrial Cu,Zn-SOD-mediated H 2 O 2 polarizes macrophages to an M2 phenotype. Conclusion: A prolonged predominance of M2 macrophages can induce a fibrotic phenotype. Significance: The antioxidant enzyme, Cu,Zn-SOD, increases mitochondrial H 2 O 2 levels, which is linked to pulmonary fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 47 publications
7
125
0
3
Order By: Relevance
“…Additionally, deficiency of p47 phox , a scaffolding protein for the NOX complex, renders macrophages hyper-responsive to IL-4-induced M2 polarization (230). Likewise, SOD1 overexpression promotes M2 polarization of alveolar macrophages (86). Together, these ex vivo studies support the significance of attenuated ROS production in development of M2 polarization state, which favors resolution of inflammation.…”
Section: Role Of Ros and Protein-s-glutathionylation In Monocyte Recrsupporting
confidence: 55%
“…Additionally, deficiency of p47 phox , a scaffolding protein for the NOX complex, renders macrophages hyper-responsive to IL-4-induced M2 polarization (230). Likewise, SOD1 overexpression promotes M2 polarization of alveolar macrophages (86). Together, these ex vivo studies support the significance of attenuated ROS production in development of M2 polarization state, which favors resolution of inflammation.…”
Section: Role Of Ros and Protein-s-glutathionylation In Monocyte Recrsupporting
confidence: 55%
“…In a recent study, we found that alveolar macrophages from asbestosis patients produce high levels of H 2 O 2 , and these cells demonstrate a predominantly pro-fibrotic M2 phenotype. Moreover, polarization to the M2 phenotype was driven, in part, by Cu,Zn-superoxide dismutase-mediated H 2 O 2 production in chrysotile-exposed cells (13). Our new observations demonstrate that chrysotile-exposed macrophages exhibit rapid and sustained increases in Ca 2ϩ release and later develop ER stress.…”
Section: Discussionmentioning
confidence: 58%
“…Similar to the pro-inflammatory state induced by ER stress in AECs (35), ER stress in macrophages has been associated with pro-inflammatory effects through activation of both a JNK-TNF␣ pathway and a CHOP-ERK-IL-6 pathway (50). When exposed to chrysotile, macrophages produce pro-fibrotic cytokines such as TGF-␤ as well as high levels of reactive oxygen species, including H 2 O 2 (13)(14)(15). In a recent study, we found that alveolar macrophages from asbestosis patients produce high levels of H 2 O 2 , and these cells demonstrate a predominantly pro-fibrotic M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, macrophages issued from Sod1 -/-mice display a pro-inflammatory profile as compared with WT macrophages (134). Inversely, in Sod1-Tg mice, where Sod1 is overexpressed and H 2 O 2 generation is enhanced, macrophages exhibit an anti-inflammatory status, associated with an increased activation of STAT6 (134), which is known to trigger the expression of antiinflammatory genes in macrophages (178).…”
Section: A Myeloid Cellsmentioning
confidence: 99%